Student and Faculty Coping and Impacts on Academic Success in Response to COVID-19 - Goldman, Jacqueline A.; Bell, Stephanie C. Bell (Journal of Interdisciplinary Studies in Education, 2022)
This study explored how faculty and students differed in their coping strategies to handle the severe stress brought on by COVID-19 and how this stress impacted student academic achievement. For this study,103 students and faculty at a rural southern university participated in the study where they reported on their coping mechanisms during the pandemic. Student grade data from midterm and final course grades were collected to measure academic achievement. Results of the study indicated that students were more likely than faculty to engage in maladaptive coping strategies, specifically emotional disengagement. The findings have theoretical and practical implications for teaching in higher education such as consideration of how students cope with severe stress compared to faculty and how it impacts academic achievement.